Challenging legitimacy at the precipice of energy calamity - Davidson, Debra J.; Gismondi, Michael Anthony; SpringerLink (Online service). (New York Springer, 2011)
Human history has often been described as a progressive relinquishment from environmental constraints. Now, it seems, we have come full circle. The ecological irrationalities associated with industrial societies have a lengthy history, and our purpose in the proposed book is not to catalogue this litany of wrongs. Rather, this book is about political responses to global environmental crisis at a crucial turning point in history, by focusing on the political discourses surrounding the tar sands in Alberta, Canada.
Electronic reproduction.
Keywords: Energy policy; Energy development -- Environmental aspects; Power resources; Environmental Studies; Electronic books